2000
DOI: 10.1177/030631200030004001
|View full text |Cite
|
Sign up to set email alerts
|

Making a Place for Science

Abstract: This paper explores the complex interaction between a group of University of California `farm advisors' and the farm community that they are meant to advise. In contrast with previous literature in science and technology studies (S&TS) on the distinctions between `laboratory science' and `field science', I show how advisors' work is a blend of these modes. More specifically, I focus on the advisors' use of `field trials' - field-based experiments conducted on growers' land - to convince their agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(13 citation statements)
references
References 1 publication
1
10
0
2
Order By: Relevance
“…Our study also echoes issues highlighted by other authors, such as the challenges of producing consent among farm advisors and farmers through field trials (Henke 2000); the need for ensuring a balance in the division of tasks and respecting opportunity costs by sharing the research budget (Hoffmann, Probst, and Christinck 2007); the observed effects of pre-analytical choices made by researchers in the project design on the efficiency of the trial process (Nederlof and Dangbégnon 2007); the importance of striking a balance between the objectives, priorities, interests, and perspectives of the different parties involved, ensuring sufficient frequency and intensity of interaction between scientists and local stakeholders, and the impact of the local stakeholders' perceived relevance of the project on the research process (Neef and Neubert 2011). These knowledge exchanges through participatory extension do, however, have also a wider potential for farmer learning and practice change in the light of sustainable farm management (Ingram 2008).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our study also echoes issues highlighted by other authors, such as the challenges of producing consent among farm advisors and farmers through field trials (Henke 2000); the need for ensuring a balance in the division of tasks and respecting opportunity costs by sharing the research budget (Hoffmann, Probst, and Christinck 2007); the observed effects of pre-analytical choices made by researchers in the project design on the efficiency of the trial process (Nederlof and Dangbégnon 2007); the importance of striking a balance between the objectives, priorities, interests, and perspectives of the different parties involved, ensuring sufficient frequency and intensity of interaction between scientists and local stakeholders, and the impact of the local stakeholders' perceived relevance of the project on the research process (Neef and Neubert 2011). These knowledge exchanges through participatory extension do, however, have also a wider potential for farmer learning and practice change in the light of sustainable farm management (Ingram 2008).…”
Section: Discussionsupporting
confidence: 84%
“…In parallel to this stream of research, there has been a growing body of studies specifically looking into the production and communication of agricultural knowledge, focusing on farmer participatory research and/or extension (Farrington and Martin 1988;Bentley 1994;van de Fliert and Braun 2002;Percy 2005;Neef and Neubert 2011) and problem-oriented approaches. While there have been some scholars that have used insights and concepts from science studies in analysing developments in the field of agriculture (see e. g. Henke 2000;Carolan 2006;Ingram et al 2018;Hansson 2019), the two streams have largely developed in isolation from each other.…”
Section: Theoretical Framework: Engaging Farmers In the Knowledge Coproduction Processmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The field trial is described as open, unpredictable, a place of variability and particularity (Kohler 2002, 6, 7). The particularities of place are not evacuated from the field trial like in a lab but have to be accounted for, that is, the prevalence of other species, topography, climate, toxins, and nutrients in the soil or the exposure to wind and sun light that shape plant growth (Henke 2000, 484).…”
Section: A Sense Of Place: the Lab And The Fieldmentioning
confidence: 99%
“…Interactions between on-station and on-farm experiments have consequently been examined from different perspectives. Some researchers focus on the balance between the scientific legitimacy of knowledge production and the relevance of the proposed techniques in real farming conditions (e.g., Henke 2000). Others underline the reciprocal inspiration among farmers' own experiments, observations made at stations, and on-farm experimentation in which farmers and researchers collaborate (Maat and Glover 2012;Périnelle et al 2021).…”
Section: Introductionmentioning
confidence: 99%